'I, the people': a deflationary interpretation of populism, Trump and the United States constitution. Issue 1 (2nd January 2017) - Singh, Robert
Abstract: This paper advances a deflationary interpretation of populism, Donald Trump and the United States Constitution. It accepts that Trump utilizes a populist pose but rejects populism as too reductive for understanding his ascension and constitutional challenge. First, it argues that, although he merits the designation, Trump reveals more about populism than populism does about him. Trump illustrates populism's conceptual elasticity, but employing it as a frame to understand him imposes coherence upon a figure whose monetized politics are chaotic, shallow and unanchored by principle. Second, populism provides a necessary but insufficient condition for critically explaining Trump's ascension, either in terms of electoral populism or populism in power. Third, while democratic deconsolidation under Trump's presidency cannot be discounted, the Constitution remains resilient in most important respects. A dispassionate constitutional sociology counsels a deflationary understanding rather than an uncritical alarmism that too frequently reproduces and reinforces the darker aspects of Trump's populist political logic.